Genome-Wide Association Study Reveals Key Genes for Differential Lead Accumulation and Tolerance in Natural Arabidopsis thaliana Accessions - Busoms, Sílvia; Pérez-Martín, Laura; Llimós, Miquel; Poschenrieder, Charlotte; Martos, Soledad (Frontiers in Plant Science, 2021)
Soil contamination by lead (Pb) has become one of the major ecological threats to the environment. Understanding the mechanisms of Pb transport and deposition in plants is of great importance to achieve a global Pb reduction. We exposed a collection of 360 Arabidopsis thaliana natural accessions to a Pb-polluted soil. Germination rates, growth, and leaf Pb concentrations showed extensive variation among accessions. These phenotypic data were subjected to genome wide association studies (GWAs) and we found a significant association on chromosome 1 for low leaf Pb accumulation. Genes associated with significant SNP markers were evaluated and we selected EXTENSIN18 (EXT18) and TLC (TRAM-LAG1-CLN8) as candidates for having a role in Pb homeostasis. Six Pb-tolerant accessions, three of them exhibiting low leaf Pb content, and three of them with high leaf Pb content; two Pb-sensitive accessions; two knockout T-DNA lines of GWAs candidate genes (ext18, tlc); and Col-0 were screened under control and high-Pb conditions. The relative expression of EXT18, TLC, and other genes described for being involved in Pb tolerance was also evaluated. Analysis of Darwinian fitness, root and leaf ionome, and TEM images revealed that Pb-tolerant accessions employ two opposing strategies: (1) low translocation of Pb and its accumulation into root cell walls and vacuoles, or (2) high translocation of Pb and its efflux to inactive organelles or intracellular spaces. Plants using the first strategy exhibited higher expression of EXT18 and HMA3, thicker root cell walls and Pb vacuolar sequestration, suggesting that these genes may contribute to the deposition of Pb in the roots. On the other hand, plants translocating high amounts of Pb showed upregulation of TLC and ABC transporters, indicating that these plants were able to properly efflux Pb in the aerial tissues. We conclude that EXT18 and TLC upregulation enhances Pb tolerance promoting its sequestration: EXT18 favors the thickening of the cell walls improving Pb accumulation in roots and decreasing its toxicity, while TLC facilitates the formation of dictyosome vesicles and the Pb encapsulation in leaves. These findings are relevant for the design of phytoremediation strategies and environment restoration.